Improving Children's Ability to Recognize Colors Through Educational Toys at Kemala Bhayangkari 01 Palu Kindergarten. - Vebrianti, Vanny; Zuama, Shofiyanti Nur; Juhriati, Ika (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2025)
The problem in this study was young children’s low ability to recognize colors, evident in difficulty naming colors and sorting and grouping objects by color. The cause was the suboptimal use of instructional media. The study aimed to improve children’s color recognition ability through the use of educational play tools at TK Kemala Bhayangkari 01 Palu. The research subjects were 15 kindergarten group A children (4 boys, 11 girls). This study used a classroom action research design with two cycles, each consisting of planning, implementation, observation, and reflection. Data were collected through observation, interviews, tasks, and documentation using observation sheets for teacher and student activities. The analysis showed that before the intervention, color recognition ability was low (categories BB, MB) with 6.67% in Very Good (BSB), 22.22% in Expected (BSH), 31.11% in Beginning (MB), and 40% in Not Yet Developed (BB). After cycles I and II, significant improvements were observed. In cycle I, BSB increased to 24.45%; BSH 35.55%; MB 20%; BB 20%. In cycle II, BSB 46.66%; BSH 40%; MB 11.11%; BB 2.23%. Thus, the use of educational play tools was proven to improve children’s color recognition ability.